Spatial and temporal correlations of thermospheric zonal winds from GOCE satellite observations - Molina, Ivana; Scherliess, Ludger (Frontiers in Astronomy and Space Sciences, 2023)
Winds in the thermosphere play an important role in the transport of momentum and energy in the upper atmosphere and affect the composition, dynamics and morphology of the ionospheric plasma. Although the general morphology of the winds is well understood, we are only starting to understand its variability. During the last decade it has become inherently clear that in addition to solar forcing of the thermosphere, the lower atmosphere also is an important driver of thermospheric variability. Therefore, an understanding of thermospheric variability and its spatial and temporal correlations is critical for an improved understanding of the coupled ionosphere-thermosphere system and the coupling to the lower atmosphere. The Gravity Field and Steady-State Ocean Explorer (GOCE) provided zonal winds near dawn and dusk at an altitude of around 260 km from November 2009 to October 2013. We have used GOCE zonal wind observations from low-to mid-latitudes obtained during geomagnetically quiet times to investigate spatial and temporal correlations in the zonal winds near dawn and dusk. Latitudinal correlations were calculated for the GOCE zonal winds for December solstice separately for each year from 2009 to 2012 and their year-to-year variation was established. Correlations between hemispheric conjugate points were found at mid latitudes during the latter years. Latitudinal correlations for December solstice 2009 and June solstice 2010 were compared and the correlation length was found to be consistently larger in the winter hemisphere during dawn and in the summer hemisphere during dusk. Zonal wind longitudinal/temporal correlations were also determined for December 2009 and 2011 and for June 2010 and found to be periodic in longitude/time. The temporal evolution of the temporal/longitudinal correlations were found to gradually decrease over the course of several days. The maxima in the correlation coefficients were always located in the winter hemisphere during dawn and in the summer hemisphere during dusk. During dawn, the largest contributors to the temporal/longitudinal correlations were found to be nonmigrating tides, whereas during dusk, additional waves appear to play important roles.